Role of thermo-mechanical gyrations on the α/β interface stability in a Ti6Al4V AM alloy - Kumar, Sabina; Vijayan, Sri Ram; Nandwana, Peeyush; Poplawsky, Jonathan D.; Yan, Chen; Babu, Sudarsanam Suresh (Scripta materialia, 2021)
Fluctuating energy distributions experienced during Additive Manufacturing yield an evolution of spatial and temporal transients within a part. In general, the in-situ monitoring of these transients is near to impossible during manufacturing. In order to then gain perspective into the impact on these localized thermo-mechanical transients on the interface stability, rapid thermo-mechanical reversals with known boundary conditions are imposed on an AM Ti6Al4V alloy which resulted in a phase transformation leading to an increased β phase stability. Our goal with this study is to comprehend the kinetics of this phase transformation with concepts of stored energy due to plastic strain accumulation and diffusion kinetics. Atom Probe Tomography is employed to study the partitioning of the solute elements across the interface. As expected, the thermo-mechanically cycled samples showed a reduced Vanadium concentration across the β phase. This concentration profile across the interface, alongside a full-width-half-max analysis, provided insight on the potential phase transformation kinetics involved in the α ➔ β transformation subject to thermo- mechanical gyrations. [Display omitted]